In Situ Laser Fenestration Is a Feasible Method for Revascularization of Aortic Arch During Thoracic Endovascular Aortic Repair. Issue 4 (April 2017) - Qin, Jinbao; Zhao, Zhen; Wang, Ruihua; Ye, Kaichuang; Li, Weimin; Liu, Xiaobing; Liu, Guang; Cui, Chaoyi; Shi, Huihua; Peng, Zhiyou; Yuan, Fukang; Yang, Xinrui; et al.
Abstract : Background: Reconstruction of the aortic major branches during thoracic endovascular aortic repair is complicated because of the complex anatomic configuration and variation of the aortic arch. In situ laser fenestration has shown great potential for the revascularization of aortic branches. This study aims to evaluate the feasibility, effectiveness, and safety of in situ laser fenestration on the three branches of the aortic arch during thoracic endovascular aortic repair. Methods and Results: Before clinical application, the polytetrafluoroethylene and Dacron grafts were fenestrated by an 810‐nm laser system ex vivo, which did not damage the bare metal portion of the endografts and created a clean fenestration while maintaining the integrity of the endografts. In vivo, 6 anesthetized female swine survived after this operation, including stent‐graft implantation in the aortic arches, laser fenestration, and conduit implantation through the innominate arteries and the left carotid arteries. Based on the animal experiments, in situ laser fenestration during thoracic endovascular aortic repair was successively performed on 24 patients (aged 33–86 years) with aortic artery diseases (dissection type A: n=4, type B: n=7, aneurysm: n=2, mural thrombus: n=7). Fenestration of 3 aortic branches was performed in 2 (8.3%) patients. Both the left carotid artery and the left subclavian artery were fenestrated in 6 (25%) patients. Only left subclavian artery fenestration surgery was done in 16 (66.7%) patients. Among these patients, 1 fenestration was abandoned secondary to an acute takeoff of the innominate artery in a type III aortic arch. The average operative time was 137±15 minutes. The technical success rate was 95.8% (n=23). No fenestration‐related complications or neurological morbidity occurred after this operation. During a mean postoperative 10‐month follow‐up (range: 2–17 months), 1 patient died of severe pneumonia, and all the left subclavian artery and carotid artery stents were patent with no fenestration‐related endoleaks upon computed tomography angiography images. Conclusions: In situ laser fenestration is a feasible, effective, rapid, repeatable, and safe option for the reconstruction of aortic arch during thoracic endovascular aortic repair, which might be available to revascularize the 3 branches. However, follow‐up periods should be extended to evaluate the robustness of this technique.